Analisis Peningkatan Kemampuan Kognitif Mahasiswa Setelah Penerapan Lms Resolva - Aditya Abdulloh Masykur; Rizky Basatha (CV. SINAR HOWUHOWU, 2026)
The learning process of Object-Oriented Programming (OOP) using Java for undergraduate students of Information Technology Education (PTI) tends to be conventional and teacher-centered. The absence of interactive media and the lack of Problem Based Learning (PBL) integration in the existing system cause students to struggle in understanding programming logic. This study aims to develop a website-based Learning Management System (LMS) named